Växtkraft, skogen som integrationsarena till arbetsmarknaden - Andersson, Andreas (2017)
During the last year at the forest master's school, a degree project will be completed on a scale of 15 higher education credits. This graduate project was sacked to investigate Sveaskog's projects Växtkraft which had as a main purpose integrate inhabitants and people with exclusion into the forest sector. A survey was conducted to investigate two different parts of this project. The one part was the role and experiences of traders through their participation in the project while the second part of the undercooling inspired the practitioners' experiences through their participation in the project.